2021
DOI: 10.3390/molecules26092633
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and Bioactive Compounds in Licorice Root Extract Potentially Contribute to Improving Growth, Bulb Quality and Yield of Onion (Allium cepa)

Abstract: The increasing culinary use of onion (Alium cepa) raises pressure on the current production rate, demanding sustainable approaches for increasing its productivity worldwide. Here, we aimed to investigate the beneficial effects of licorice (Glycyrrhiza glabra) root extract (LRE) in improving growth, yield, nutritional status, and antioxidant properties of two high-yielding onion cultivars, Shandaweel and Giza 20, growing under field conditions in two consecutive years. Our results revealed that pretreatments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 69 publications
(86 reference statements)
2
5
0
Order By: Relevance
“…One more crucial mechanism operative in plants is an adaptation to salinity stress by regulating the antioxidant defense system by inducing ascorbate (ASA) and glutathione (GSH), which are important for eliminating ROS and maintaining cellular redox potential (Younes et al 2021), as shown in our results. In our study, the contents of ASA and GSH were elevated in response to the formation of H 2 O 2 to counteract oxidative damage in salinity-stressed plants.…”
Section: Discussionsupporting
confidence: 66%
“…One more crucial mechanism operative in plants is an adaptation to salinity stress by regulating the antioxidant defense system by inducing ascorbate (ASA) and glutathione (GSH), which are important for eliminating ROS and maintaining cellular redox potential (Younes et al 2021), as shown in our results. In our study, the contents of ASA and GSH were elevated in response to the formation of H 2 O 2 to counteract oxidative damage in salinity-stressed plants.…”
Section: Discussionsupporting
confidence: 66%
“…They reported that 0.50 % of the biostimulant extract elevated height, crop growth rate, number of leaves, bulb fresh weight, harvest index, chlorophyll a and b, leaf protein content, bulb protein content and high bulb yield in onion. Younes et al, (2021) have reported that liquorice root extract application in onion acts as a biostimulant and elevates the growth, yield, and quality parameters in onion. They have also shown improved nutritional status, total soluble carbohydrates, proline level, water-soluble proteins and activated the enzymatic and non-enzymatic antioxidants level in onion bulbs.…”
Section: Biostimulantsmentioning
confidence: 99%
“…One crucial mechanism evolved by plants to adapt to salinity stress includes the induction of enzymatic and non-enzymatic antioxidants, which are important for eliminating ROS and maintaining cellular redox potential [ 14 , 77 ]. Under abiotic-induced oxidative stress, SOD scavenges O⋅ − into O 2 and H 2 O 2 as the first stage of the defense system, and the peroxidases act on the generated H 2 O 2 reducing it to H 2 O.…”
Section: Discussionmentioning
confidence: 99%